PENINGKATAN KUALITAS DAN DAYA SAING PRODUK GULA NIRA MELALUI TEKNOLOGI PANGAN DAN STRATEGI REBRANDING PADA KELOMPOK TANI SERBA USAHA, DESA HARGOROJO, PURWOREJO - Wajar Bimantoro; Yudha Riwanto; Bambang Pilu Hartato (Jurnal Abdi Insani, 2026)
This community service activity was motivated by the low quality and competitiveness of palm sap sugar products produced by the Serba Usaha Farmer Group in Hargorojo Village, Purworejo. The main issues included unhygienic traditional production methods, unstable moisture content, and unattractive packaging and branding. The objective of this program was to improve the quality and competitiveness of palm sap sugar through the application of food technology using a sugar drying machine and an integrated rebranding strategy. The methods involved field observation, training on the use of the drying machine to achieve standardized moisture levels, mentoring in packaging and label design, and evaluation of implementation results. The outcomes showed a significant improvement in product quality, characterized by drier texture, more uniform color, and longer shelf life. Furthermore, the farmer group gained a better understanding of the importance of process standardization and visual branding in enhancing market appeal. The rebranded product received positive feedback from local consumers and began to be distributed to regional souvenir shops. In conclusion, the application of a sugar drying machine as a simple food technology combined with rebranding strategies effectively improved the quality, added value, and competitiveness of palm sap sugar products.